107k views
0 votes
Solve the equation for x. (5 points)

the square root of the quantity x minus 6 end quantity plus 3 equals 10

1 Answer

0 votes

Solution:

I think the equation should be:


√(x - 6) + 3 = 10

If so, collect like terms to make x the subject of formula.


√(x - 6) = 10 - 3 \\ √(x - 6) = 7

Square both sides due to the presence of square root.


( √(x - 6) {)}^(2) = (7 {)}^(2)


x - 6 = 49

Collect like terms.


x = 49 + 6

Therefore:
x = 55

I hope this helps.

User Lairtech
by
5.7k points